Vitamin D deficiency: a risk factor for myopia in children: a cross sectional study in a tertiary care centre - Aaraj, Sahira; Kausar, Ayisha; Khan, Sabeen Abid (Journal of the Pakistan Medical Association, 2022)
Objective: To study the role of vitamin D deficiency as a risk factor for myopia in children aged 5-15 years. Method: The cross-sectional observational study was conducted from January to September 2019 at the Ophthalmology and Paediatric departments of Shifa Foundation Community Health Centre, Islamabad, Pakistan, and comprised patients with suspected / symptomatic vitamin D deficiency who were enrolled from the paediatric outpatient department and referred to the ophthalmology clinics for eye exam. Apart from taking detailed ocular history, slit lamp examination, Snellen’s distance visual acuity, auto-refraction to calculate spherical equivalent, and amplitude scan for measuring the axial length were performed. An average of 3 measurements was taken for both refraction and axial length calculation. Myopia was labelled if mean spherical equivalent was 0.25 dioptres. Vitamin D deficiency was defined as serum 25 hydroxyvitamin D level <20ng/ml. Data was analysed using SPSS 23. Results: There were 72 subjects with a mean age of 10.11±2.69 years; 37(51.4%) boys and 35(48.6%) girls. Myopia was seen in 40(55.6%) patients, while 32(44.4%) were emmetropic. The overall mean vitamin D level was 20.25±12.18 ng/ml. There was no significant association between myopia and vitamin D deficiency (p=0.115). Significant associations were found between myopia and relatively older age (p=0.005), higher height (p=0.001), more weight (p=0.001) and higher body mass index value (p=0.008). Conclusion: Low vitamin D levels were not significantly associated with myopia in children aged 5-15 years, but significant associations were found between myopia and relatively older age, and various anthropometric measures.